Rekognisi dan Kewarganegaraan di Indonesia: Analisis terhadap Program Peduli Lakpesdam NU - Amin Mudzakkir (Tashwirul Afkar, 2021)
In the contemporary era, recognition or recognition is very crucial. However, instead of understanding it only culturally, recognition includes broad dimensions, including attempts to place one's or group's status in social and economic structures. This understanding derived from Nancy Fraser is used to analyze the activities of the Lakpesdam PBNU "care" program from 2015 to 2020. Based on the available activity documents, including minutes from various regions, this paper shows the importance of recognition in a more structural sense as a more efficient way of working. effective way to include vulnerable groups in Indonesia in citizenship discourse and practice.